Selective fishing and balanced harvesting - Breen, Mike; Graham, Norman; Pol, Michael; He, Pingguo; Reid, Dave; Suuronen, Petri (Elsevier, 2016)
Fishing is by nature and design selective, targeting species and sizes that yield the highest economicreturns. Manipulation of the selective characteristics of fishing gear has been an important tool to influ-ence the fishing pattern-for example, to minimise capture of certain age groups or to minimise catchesof unwanted species. Selective removal of specific species and age groups in preference to others maycontribute to changes in the species and size composition of fish communities, alter trophic interac-tions, and may lead to phenotypic or genotypic changes in harvested stocks. Balanced harvest (BH) is anecologically based concept that aims to balance fishing mortality across a range of species, stocks andsizes, in proportion to their natural productivity in an ecosystem, so that the relative size and speciescomposition are maintained relative to an unexploited ecosystem. The BH concept suggests that man-agement practices and markets that promote size and species selective fishing should be reconsidered;as such it has been misinterpreted by some as an unselective fishing strategy. However, selectivity infisheries is complex, and we introduce a multi-level concept of selective fishing to describe and discussthis unrecognized complexity, and examine the feasibility of a BH-type strategy. We conclude that a BHis an interesting concept that merits further exploration to better understand the challenges towardspragmatic implementation. Contrary to some interpretations of the BH concept, its implementation mayrequire even more selective fishing gears and practices.
Keywords: balanced harvesting; selective fishing; harvesting pattern; sustainable fisheries; harvesting; fishing; sustainable fishery